IMPLEMENTATION OF PEDAGOGIC COMPETENCE THROUGH HUMANIST LEARNING PERSPECTIVE OF KI HADJAR DEWANTARA - Gilang Arya Alghifari; Fahmi Ibrahim; Muhamad Parhan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Education aims to construct students to become independent human beings physically and spiritually. To make this happen, educators must have pedagogic competence, which is necessary to support them as professional educators. The pedagogic concept is inseparable from a well-known figure in the world of education, namely Ki Hadjar Dewantara, who gave birth to the concepts of Momong, Among, and Ngemong, based on the concept of humanist education that shows the cultural characteristics of the Indonesian nation. The research method used is qualitative with a Case Study approach, which aims to find out the humanist concept of increasing teacher understanding. The research results indicate that to understand and protect the needs of students, it is necessary to understand pedagogical competency standards to become professional educators, and educators need to be involved in self-development, and collaboration in achieving humanist learning that includes students’ understanding, class management skills, and the ability to provide constructive feedback by determining one of which that refers to the educational concept of Ki Hadjar Dewantara.